Knowledge, attitudes, and behaviors of practitioners supporting cancer patients in fertility preservation in DKI Jakarta: A cross-sectional study - Achmad Kemal Harzif; Raymond Surya; Raden Muharam; Gita Pratama; Alfa Putri Meutia (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: More than 135,000 people aged under 45 yr are diagnosed with cancer annually in Indonesia. Good detection and management of cancer increase the quality of life. Objective: To determine the knowledge, attitudes, and behaviors of practitioners supporting cancer patients in fertility preservation. Materials and Methods: This cross-sectional study was conducted in 18 type D government hospitals and Dr. Cipto Mangunkusumo Hospital, in Jakarta, Indonesia, between January 2018 and August 2019. This study involved practitioners providing care to cancer patients. Data were described descriptively. Results: Most of the general practitioners, specialists, and subspecialists who participated in this study were aged 26-30 yr (65.4%), 31-35 yr (70.4%), and 31-40 yr (53.0%), respectively. The fertility treatment most known by general practitioners was in vitro fertilization with embryo cryopreservation (12.1%); for specialists it was sperm cryopreservation (24.5%). Meanwhile, subspecialists knew most about in vitro fertilization with embryo cryopreservation and sperm cryopreservation using a GnRH agonist (such as leuprolide injection) pre-cancer treatment (13%). A positive attitude towards fertility preservation as an important priority for cancer patients was shown in 72.0% of general practitioners, 73.3% of specialists, and 100% of subspecialists. General practitioners mostly referred patients to fertility specialists (44.4%). Many specialists (54.9%) and subspecialists (67%) discussed the possible impact of the patient's condition and / or treatment on fertility. Conclusion: The knowledge of and practices related to fertility preservation differed among general practitioners, specialists, and subspecialists. However, positive attitudes among them were similar.